Autonomic Nervous System Function in Newly Diagnosed Multiple Sclerosis: Association With Lipid Levels and Insulin Resistance - Hardoňová, Miroslava; Šiarnik, Pavel; Siváková, Monika; Suchá, Bianka; Vlček, Miroslav; Imrich, Richard; Turčáni, Peter; Havranová, Andrea; Rádiková, Žofia; Žitňanová, Ingrid; Dean, Zuzana; Penesová, Adela; et al. (Physiological research, 2021)
Autonomic nervous system (ANS) disorders are common in multiple sclerosis (MS). Previous studies showed differences in insulin resistance (IR) and lipoprotein levels in MS subjects compared to controls. Lipolysis caused by increased sympathetic activity could be one of the possible linking mechanisms leading to dyslipidemia in MS. Our study aimed to evaluate ANS activity in the context of glucose and lipid metabolism in people with MS. We prospectively measured short-term heart rate variability (HRV), fasting lipoprotein concentrations, and calculated IR indices based on plasma glucose and insulin levels during oral glucose tolerance test (oGTT) in 32 patients with MS and 29 healthy controls matched for age, sex and body mass index in our study. There was no significant difference in HRV parameters and lipoprotein levels between MS and controls. A significant positive correlation was found between low/high-frequency power ratio (LF/HF) and triglycerides (r=0.413, p=0.021) in MS subjects but not in controls. A significantly lower whole-body insulin sensitivity index (ISIMat) was found in patients with MS compared to the control group (7.3±3.7 vs. 9.8±5.6, p=0.041). No significant correlations were found between LF/HF and IR parameters. In MS subjects, the positive correlation of LF/HF with triglycerides could reflect the effects of sympathetic activity on lipolysis. Positive correlations of sympathetic activity with increased lipoprotein levels could rather reflect processes associated with immune system activation/inflammation, than processes involved in glucose homeostasis maintenance.
Keywords: dospělí; Female; autonomní nervový systém; Autonomic Nervous System; Adult; mladý dospělý; ženské pohlaví; lipidy; lidé; Multiple Sclerosis; lipolýza; roztroušená skleróza; Lipids; prospektivní studie; Male; Prospective Studies; Young Adult; Insulin Resistance; inzulinová rezistence; mužské pohlaví; Lipolysis; Humans